Acculturation, Integration, food knowledge, food media, food for social events / Reezlin Abdul Rahman, Mohamad Amer Hasbullah and Mohd Salehuddin Mohd Zahari - Abdul Rahman, Reezlin; Hasbullah, Mohamad Amer; Mohd Zahari, Mohd Salehuddin (2016)
Many technical institutions in this era are seriously focusing on providing the individuals, especially the young with solid skills through hands-on or practical ability. This approach, as argued by many scholars is more holistic enable students to meet the industry need and increase their employability rates. The implementation of the modular system is one of the ways to master students' skills and improve practical knowledge in specific areas. This study empirically investigates the effectiveness of basic western cuisine as part of the culinary arts modular program in Malaysia community colleges toward students’ psychomotor performance. Using triangulation approach of self-completed questionnaire and interview, some useful insights were obtained. The introduction of the basic western cuisine module is creating promising outcomes. The module is gradually enhancing students’ knowledge, skills, confidence level and psychomotor performance, which enable them to at least prepare the western food ranging from breakfast cookery to simple appetizers, main courses, and desserts. This positive indication, although in the early stage has given the implications for students, lecturers, parents, ministry of higher education, hospitality and foodservice industry in general.